Post COVID-19 Vaccination Side Effects and Associated Factors Among Vaccinated Clients in Bahir Dar City, Ethiopia - Ebrahim Abdela Siraj MSc; Ashagrachew Tewabe Yayehrad MSc; Zewdu Yilma MSc; Tamyalew Getahun MSc; Mequannent Sharew Melaku MSc; Gizachew Kassahun Bizuneh MSc; Zemene Demelash Kifle MSc; Dawit Kumilachew Yimenu MSc (SAGE Publishing, 2023)
Introduction The lack of local side effect profiles for vaccines could hinder vaccination uptake. Since all COVID-19 vaccines are brand-new medications, it is crucial to keep track of any safety related concern. Objective This study is aimed to investigate post-vaccination side effects of COVID-19 vaccines and associated factors in Bahir Dar city. Method An institutional-based cross-sectional study was conducted among vaccinated clients. A simple random and a systematic random sampling method were used to select the health facilities and the participants, respectively. Bi-variable and multivariable binary logistic regression analyses were executed with odds ratio at 95% confidence intervals at p  < .05. Results A total of 72(17.4%) participants reported at least one side effect following vaccination. The proportion prevalence was higher after the first dose than that of the second dose and the difference was also found to be statistically significant. In the multivariable logistic regression analysis female participants (AOR = 3.39, 95% CI =  1.53, 7.52), participants with a history of regular medication use (AOR = 3.34, 95% CI  =  1.52, 7.33), participants aged 55 and above (AOR = 2.93, 95% CI  =  1.23, 7.01), and participants who had taken only the first dose (AOR = 14.81, 95% CI  =  6.40, 34.31) were more likely to develop side effects for COVID 19 vaccination compared to their counterparts. Conclusion A significant number (17.4%) of participants reported at least one side effect following vaccination. Sex, medication, occupation, age, and type of vaccination dose were factors statistically associated with the reported side effects.